The freeze-drying of Cowdria ruminantium - du Plessis, J L; van Gas, L; Labuschagne, F J; Wijma, S (Onderstepoort journal of veterinary research, 1990)
Lyophilized tissues of mice and blood of sheep, infected with either the Kümm, the Welgevonden or the Ball 3 stock of Cowdria ruminantium, remain infective to mice and sheep after storage at 4 degree C for 90 days. Freeze-dried tissues stored at -18 degrees C and -28 degrees C are still infective after 6 months and 2 years, respectively.